2017
DOI: 10.1063/1.4975103
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding DNA condensates produced by DNA-like charged depletants: A force spectroscopy study

Abstract: In this work, we have measured, by means of optical tweezers, forces acting on depletion-induced DNA condensates due to the presence of the DNA-like charged protein bovine serum albumin (BSA). The stretching and unfolding measurements performed on the semi-flexible DNA chain reveal (1) the softening of the uncondensed DNA contour length and (2) a mechanical behavior strikingly different from those previously observed: the force-extension curves of BSA-induced DNA condensates lack the "saw-tooth" pattern and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In other words, the contour length decreases by ∼50% when using only BSA (without doxo). This is the lowest value found for this parameter under our experimental conditions, as shown in Ref …”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…In other words, the contour length decreases by ∼50% when using only BSA (without doxo). This is the lowest value found for this parameter under our experimental conditions, as shown in Ref …”
Section: Resultssupporting
confidence: 61%
“…As known, a considerable energetic cost (due to enzyme action) is needed in vivo to open and unzip the double‐helix. In addition, it was previously demonstrated that the presence of BSA in the buffer suppresses DNA overstretching transition found at high forces (∼65 pN), thus stabilizing the double‐helix structure. Such result corroborates with the conclusion drawn above.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations